Correction: Carbon onion/sulfur hybrid cathodes via inverse vulcanization for lithium–sulfur batteries. Issue 7 (9th March 2022) - Choudhury, Soumyadip; Srimuk, Pattarachai; Raju, Kumar; Tolosa, Aura; Fleischmann, Simon; Zeiger, Marco; Ozoemena, Kenneth I.; Borchardt, Lars; Presser, Volker
Abstract : Correction for 'Carbon onion/sulfur hybrid cathodes via inverse vulcanization for lithium–sulfur batteries' by Soumyadip Choudhury et al., Sustainable Energy Fuels, 2018, 2, 133–146, DOI: ; 10.1039/C7SE00452D .